2015
DOI: 10.12989/aas.2015.2.4.469
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the performances of a heat exchanger in a light helicopter

Abstract: This study has the aim to develop a numerical design regarding the position and the inner performances of a heat exchanger in a light helicopter. the problem was to find first of all the best position of the heat exchanger inside the engine vane in order to maximize the air flow rate capable to pass through the heat exchanger section. It is to be said that the only air contribution in the vane comes from the opening present in the roof under the main rotor. The design has been performed by means of the commerc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…• StarCCM+, They include packages able to simulate the flow fields inside the tubes and also specific numerical models capable of simulating special fluids like nanofluids or special structures like porous media [23][24][25][26].…”
Section: Numerical Toolsmentioning
confidence: 99%
See 2 more Smart Citations
“…• StarCCM+, They include packages able to simulate the flow fields inside the tubes and also specific numerical models capable of simulating special fluids like nanofluids or special structures like porous media [23][24][25][26].…”
Section: Numerical Toolsmentioning
confidence: 99%
“…The relationship between the mass flow rate _ m and pressure drop ∆p in the cooler can be put in a similar shape, see the values shown in Table 2 where Δn is the HE total length in the flow direction, ρ is the air density, and μ is the air dynamic viscosity, see papers [23][24][25][26]. By using the aforementioned values, one can simulate the external and internal flow fields with respect to the cooling ducts and find the numerical air flow rate passing through the heat exchanger.…”
Section: Heat Exchanger Efficiency In a Pusher Enginementioning
confidence: 99%
See 1 more Smart Citation
“…They reported that natural convection and flow field are significantly affected by (Ra) and fin thickness. Carozza [18] developed a numerical model to simulate air flow through a heat exchanger inside the engine vane of a helicopter. The best place of heat exchanger is found to be near the lower exit on the rear to increase the air flow rate.…”
Section: Introductionmentioning
confidence: 99%